The Effect of MU Hypertension Herbal Drink and A 30-Minute Walk on Blood Pressure - Nur Hidayati; Meynkha Cindy Arby Dahnia; Aprelia Afidatul Hanafi (Indonesian Journal of Global Health Research, 2025)
Hypertension among elderly may result in a number of complications if left untreated. Objective to determine the effect of giving MU hypertension herbal drink and 30 minutes of walking to reduce blood pressure. Quasi-experimental with two groups pre and post test. The study sample was 60 elderly (intervention= 30; control= 30), which was selected using purposive sampling technique. The intervention group was given MU hypertension tea and walked for 30 minutes, while the control group was only given MU hypertension tea, for 7 days each. Data was collected in April-May 2025, then analysed by Wilcoxon and Mann Whitney test (≤0.05). The intervention group experience decrease in average systolic and diastolic blood pressure of 43.87 and 30.36 mmHg. The control group experience decrease in mean systolic and diastolic blood pressure of 40.8 and 26.16 mmHg. Differences in systolic blood pressure before and after treatment in both groups (p = 0.000; p = 0.000) is found. Differences in post-test systolic and diastolic blood pressure between two groups (p = 0.000; p = 0.000) is found. MU hypertension tea and 30 minutes of walking have been proven to be effective to lowering blood pressure in the elderly.